The role of rhizome system in the distribution of cadmium load among ramets of Phragmites australis - Bankó László; Ördög Mónika; Erdei László; Hungarian Congress on Plant Physiology, 7., 2002, Szeged (2002)
The common reed, Phragmites australis (Cav.) Trin. ex Steud., is a clonal plant which is sensitive to environmental disturbances. A clone is composed of large number of ramets which are physically interconnected. In this work the translocation of cadmium from a selected ramet towards the rhizome network of 15 to 30 ramets was investigated in model experiments with known rhizome systems. At the site of treatment, Cd2+ uptake was much higher both in the roots and rhizome than in the shoot, however, at the distal ramets, shoots accumulated higher concentration of Cd2+ than roots and rhizomes, and the ramets at the farthest site contained the highest levels of Cd2+. The control of transport through the rhizome network by the distal ramet so far has not been described. The mechanism by which the farthest ramet attracts the heavy metal remains to be investigated.